2017
DOI: 10.1002/tox.22456
|View full text |Cite
|
Sign up to set email alerts
|

Microcystin‐LR disrupts insulin signaling by hyperphosphorylating insulin receptor substrate 1 and glycogen synthase

Abstract: Microcystin-LR (MC-LR) is a cyanobacteria-derived heptapeptide that has been commonly characterized as a hepatotoxin. Although the liver is a primary organ in glucose homeostasis, the effect of MC-LR on glucose metabolism remains unclear. In this study, the human liver cell line HL7702and ICR mice were exposed to various concentrations of MC-LR for 24 h, and the proteins involved in insulin signaling were investigated. The results showed that MC-LR treatment induced the hyperphosphorylation of insulin receptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 47 publications
3
8
0
Order By: Relevance
“…GSK‐3 is a key kinase responsible for GS (Ser 641) phosphorylation . In the current study, Ser 641 in GS was observed to be hyperphosphorylated, even when the activity of GSK‐3 decreased, which was out of our expectations but was similar to our previous results obtained in HL7702 cells and livers from mice with 24 hours of being exposed to the MC‐LR . However, the result can be explained by the complex regulation of GS activity, which is controlled by multiple crosstalk pathways or molecules in a cell.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…GSK‐3 is a key kinase responsible for GS (Ser 641) phosphorylation . In the current study, Ser 641 in GS was observed to be hyperphosphorylated, even when the activity of GSK‐3 decreased, which was out of our expectations but was similar to our previous results obtained in HL7702 cells and livers from mice with 24 hours of being exposed to the MC‐LR . However, the result can be explained by the complex regulation of GS activity, which is controlled by multiple crosstalk pathways or molecules in a cell.…”
Section: Discussionsupporting
confidence: 87%
“…The activity of S6K1 is responsible for the hyperphosphorylation of many serine sites in IRS1, such as Ser 1101, Ser 636, Ser 616, Ser 527, Ser 323, Ser 312, Ser 307, and Ser 270 in humans and Ser 1097, Ser 635/632, Ser 318, and Ser 302 in mice, which blocks IRS1 activity and interrupts downstream signaling. In our previous study, IRS1 was hyperphosphorylated at the Ser 302, Ser 318, and Ser 1097 sites in livers of mice receiving 24 hours of treatment by MC‐LR . Here, there was a similar result for mice receiving 1 hour of treatment by MC‐LR.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations